Invention Patently Obvious. - Kirk Teska
Generally speaking, in order to be patentable an invention has to be both new and unobvious. While newness is a fairly easy objective determination, unobviousness necessarily involves a subjective determination. This paper presents two controversial inventions and their patents to illustrate the issues involved in determining obviousness. The first case involves the Furminator pet grooming tool, while the second case involves a novel power supply system for document and image scanners. The paper also focuses on the current case pending before the US Supreme Court involving Teleflex and its competitor, KSR International. The Supreme Court is tasked to decide whether a combination of preexisting components, wherein those components individually do nothing more than what they were designed to do, is patentable
Keywords: Furminator pet grooming tool; KSR International; Teleflex; Document scanners; Image scanners; Inventions; Objective determination; Power supply system; Subjective determination